Early Molecular Mechanisms Involved Post Cochlear Implant Electrode Insertion Trauma. (23rd August 2013) - Eshraghi, Adrien A.; Gupta, Chhavi; Granham, Carolyn; Van De Water, Thomas; Telischi, Fred F.; Lang, Dustin
Abstract : Objectives: Cochlear implant electrode insertion trauma (EIT), not only causes direct tissue trauma and cell losses by necrosis, but also generates programmed cell death (PCD) and can lead to a loss of residual hearing. We aimed to: 1) Analyze the molecular mechanisms involved in PCD of hair cell (HCs) and support cells (SCs). 2) Compare the time of onset of these events in HCs and SCs. Methods: Guinea pigs were categorized in three groups: EIT; pre‐treated with AM‐111 at round window ½ hr before EIT, and unoperated contralateral ears as controls. Immunostaining for phospho‐c‐Jun, activated Caspase‐3, CellROX, HNE and Reactive nitrogen species (RNS) were performed at 6hrs, 12hrs and 24hrs post‐EIT. Results: At 6 hrs Post‐EIT immunostaining SCs is positive for phosphorylation of c‐Jun and activation of caspase‐3. p‐c‐Jun labeling was observed at 12 hrs in both HCs and SCs of middle and basal turn. Caspase‐3 activation was not observed in HCs of any turn. Lipid peroxidation starts 12hrs post EIT in both HCs and SCs of basal turn, and reaches up to apex turn at 24hrs post EIT. Conclusions: PCD starts initially in the SCs post EIT, followed by PCD in HCs. Caspase 3 activation is observed only in SCs. Protecting SCs with selective otoprotective drugs at early stage post implantation may help to preserve HCs and residual hearing.